PENAMBAHAN PUPUK KOMERSIAL PADA MEDIUM BBM UNTUK PERTUMBUHAN SPIRULINA PLANTENSIS DAN UJI AKTIVITAS ANTIOKSIDAN - Elida Mardiah; Nur Fadillah Pulungan; Marniati Salim (Lembaga Penelitian Universitas Trisakti, 2019)
The productivity and quality of Spirulina platensis is determined by the medium growth. One nutrient that can be used for growth Spirulina platensis microalgae are commercial fertilizers including Urea, ZA and TSP. The nitrogen contained in Urea and ZA fertilizers and phosphate in TSP fertilizer will used as an additional nutrient into the growth medium. This research aims to optimize the Spirulina platensis growth medium and test antioxidant activity. Spirulina platensis extract is obtained by sonication and maceration with methanol solvent. The antioxidant activity test was carried out withcalculate IC.50 by spectrophotometry by method1, 1-diphenyl-2-picrylhydrazyl (DPPH). The results showed that fertilizervariations ontreatments P1, P2, P3, P4, P5 and P6 provide optimum growthattreatment P5 (40% urea, 10% ZA and 40% TSP). Spirulina platensis growthon BBM, P5 and BBM medium combined with P5highest cell density on different days of growth. highest is availableon medium C (50% BBM + P5 50%) on day 11. Antioxidant activity inmedium C69,103m g / l, antioxidant activities are classified strong.